Manusia Sempurna: Studi atas Konsep Manusia Multi Dimensi Menurut Murtadha Muthahhari - Syamsuri Syamsuri (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This article discusses Murtadha Muthahhari’s ideas about the perfect or multidimensional human and the methods to develop these dimensions to attain the status of a perfect human. Murtadha Muthahhari argues that humans consist of two main elements, namely the individual and personality (body and soul, or physical and mental). These two elements have very different qualities and characteristics. The soul element is eternal and always drives humans to do good, maintain purity and honor, and always desire closeness to God. Meanwhile, the bodily or physical element, in contrast to the soul element, drives humans to fulfill material needs and tends towards lowliness, degradation, and even distance from God.